Oxford dictionary of biochemistry and molecular biology - Smith, Anthony D. (Anthony Donald) 1926- (Oxford University Press, 1997)
"The Oxford Dictionary of Biochemistry and Molecular Biology provides a comprehensive survey of current biochemistry and molecular biology. The entries are short but informative, providing up-to-date information on a broad range of topics. There are over 17,000 main entries, which give details of biochemical substances and the processes in which they are involved, define methods and concepts in molecular biology, and give definitions of biochemical symbols and abbreviations. Alternative names for biochemical compounds are listed and will refer the reader to the main entry where the internationally recommended biochemical nomenclature is used. Entries also include the structures and activities of chemical compounds of interest to biochemists, with over 800 illustrations of chemical structures. The Dictionary contains over 2000 protein and enzyme entries, which describe the functions they perform and/or the reactions they catalyse and include database codes to facilitate locating their entries in sequence databases. Brief biographical details are provided for relevant Nobel Laureates and for eponyms." "The Oxford Dictionary of Biochemistry and Molecular Biology will serve as a reference for biochemists and molecular biologists seekinginformation outside their own fields, and for those wishing to revisit fundamental principles."--Jacket.